ANALISIS REKAM MEDIS ELEKTRONIK DALAM MENUNJANG EFEKTIVITAS KERJA DI UNIT REKAM MEDIS DI RUMAH SAKIT HERMINA PASTEUR - Aulia, Az-Zahra Rizky; Sari, Irda (Jurnal Infokes, 2023)
Electronic medical records are an important achievement of information technology in the world of health and have considerable benefits, one of which is to increase the effectiveness of officer work. The use of electronic medical records at Hermina Pasteur Hospital is still not perfect and there are still several obstacles that can hinder the effectiveness of officers’ work. The purpose of this study was to determine the analysis of electronic medical records in supporting work effectiveness in the medical records unit at Hermina Pasteur Hospital Bandung. This research uses descriptive qualitative methods with data collection techniques with observation, interviews, literature studies and questionnaires. The results of this study showed security aspects (91.7%), integrity aspects (82.8%), availability aspects (87.1%), work quality aspects (81.7%), work quantity aspects (79.6%), and work time (86.1%). The suggestions given in this study are: It is necessary to evaluate the use of electronic medical records so that appropriate training can be carried out, carry out routine system maintenance, coordinate with related electronic medical record vendors to update the electronic medical record system, legalize electronic signatures and provide electronic signature tools, hospitals should provide automatic generators for better electricity availability, it is necessary to hold SPO on electronic medical records so that electronic medical records in hospitals can be ensured that they meet the established security, privacy and quality standards.